2019
DOI: 10.1038/s41598-019-49800-y
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Effect of Total Dissolved Gas-Supersaturated Water with Suspended Sediment on River Sturgeon (Acipenser dabryanus)

Abstract: High total dissolved gas (TDG) levels and excessive suspended sediment (SS) concentrations pose serious threats to fish survival during flood season. However, little information is available on the effects of TDG supersaturation with varying SS concentrations on fish. In this study, laboratory experiments were performed to investigate the effects of TDG supersaturation with varying SS concentrations on five-month-old river sturgeons (Acipenser dabryanus). The test fish were exposed to combinations of SS concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Previous laboratory studies also showed that juvenile Leptobotia elongata had a better tolerance than juvenile Schizothoracin prenanti (Wang et al, 2015; Yuan et al, 2017). Of the endemic species in China, juvenile Leptobotia elongata and Schizothoracin prenanti have a longer semi‐lethal time than other species when exposed to TDGS (Cao et al, 2016; Feng et al, 2019; Liu et al, 2019). The results of this study suggest that more deaths may occur for other endemic Chinese fish during flood discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous laboratory studies also showed that juvenile Leptobotia elongata had a better tolerance than juvenile Schizothoracin prenanti (Wang et al, 2015; Yuan et al, 2017). Of the endemic species in China, juvenile Leptobotia elongata and Schizothoracin prenanti have a longer semi‐lethal time than other species when exposed to TDGS (Cao et al, 2016; Feng et al, 2019; Liu et al, 2019). The results of this study suggest that more deaths may occur for other endemic Chinese fish during flood discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the effect of gas supersaturated water on Oncorhynchus tshawytscha, Oncorhynchus and Salmo gairdneri were investigated in the Nechako River and the Columbia River [ 2 , 11 ]. In China, some studies have been carried to estimate the effect of TDG on endemic species of Yangtze River (e.g., Acipenser dabryanus, Schizothorax prenanti and Procypris rabaudi ) in the laboratory [ 17 , 18 , 19 ]. However, relatively few studies have investigated the effect of TDG supersaturation on fish in natural rivers.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation for this finding is that the compensation depth of water decreased the development of GBD [ 34 ]. Previous research demonstrated that higher TDG level (>125%) led to high mortality (nearly 100%) in fish after 96 h of exposure [ 13 , 19 , 22 , 31 ]. Relatively high survival probabilities for juvenile Procypris rabaudi and juvenile Myxocyprinus asiaticus were observed in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations